Green synthesis of polysaccharide stabilized gold nanoparticles: chemo catalytic and room temperature operable vapor sensing application - Tagad, Chandrakant K.; Rajdeo, Kishor S.; Kulkarni, Atul; More, Pooja; Aiyer, Rohini C.; Sabharwal, Sushma G. (RSC Advances, 2014)
A facile, one pot, completely green, and cheap route for the synthesis of gold nanoparticles (AuNPs) has been developed by using locust bean gum (LBG), both as a reducing and a stabilizing agent. Synthesized AuNPs were characterized by UV-vis spectroscopy, TEM, XRD, dynamic light scattering analysis (DLS) and EDAX. A characteristic surface plasmon peak at 537 nm confirmed the formation of AuNPs. Synthesized AuNPs were found to be an efficient catalyst for the reduction of 4-nitrophenol (4-NP) to 4-aminophenol (4-AP). The reaction follows pseudo-first order kinetics with a rate constant of 14.46 X 10(-2) min(-1). Furthermore, the catalytic efficiency of AuNPs for ethanol vapor sensing was investigated by doping AuNPs in a tin oxide (SnO2) matrix synthesized by a single step thermal decomposition method. The AuNPs doped SnO2 sensor showed a fast response (similar to 5 seconds) and excellent ethanol sensing behavior in the range of 10 to 120 ppm at room temperature. A two fold increase in ethanol vapor sensing response was observed with AuNPs doped SnO2 as compared with the pure SnO2 sensor.